2017
DOI: 10.1021/acschemneuro.7b00272
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evaluation of Novel Bioisosteres of an Adamantanyl Benzamide P2X7 Receptor Antagonist

Abstract: Adamantanyl benzamide 1 was identified as a potent P2XR antagonist but failed to progress further due to poor metabolic stability. We describe the synthesis and SAR of a series of bioisosteres of benzamide 1 to explore improvements in the pharmacological properties of this lead. Initial efforts investigated a series of heteroaromatic bioisosteres, which demonstrated improved physicochemical properties but reduced P2XR antagonism. Installation of bioisosteric fluorine on the adamantane bridgeheads was well tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
(28 reference statements)
2
30
0
Order By: Relevance
“…Studies over the past decades have collected substantial evidence to support the importance of alterations in the innate immune system function in the pathophysiology of mood disorders (Bauer et al, 2014;Bhattacharya and Drevets, 2017;Brown et al, 2017;Dantzer et al, 2008;Iwata et al, 2013;Jones and Thomsen, 2013;Kaufmann et al, 2017;Maes et al, 2012;Raison et al, 2006;Slavich and Irwin, 2014;Wohleb et al, 2016;Yirmiya et al, 1999). For example, there were significant increases in the expression of NLRP3 and caspase-1 in blood cells from MDD patients (Alcocer-Gomez et al, 2014).…”
Section: The Inflammation Hypothesis Of Mood Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies over the past decades have collected substantial evidence to support the importance of alterations in the innate immune system function in the pathophysiology of mood disorders (Bauer et al, 2014;Bhattacharya and Drevets, 2017;Brown et al, 2017;Dantzer et al, 2008;Iwata et al, 2013;Jones and Thomsen, 2013;Kaufmann et al, 2017;Maes et al, 2012;Raison et al, 2006;Slavich and Irwin, 2014;Wohleb et al, 2016;Yirmiya et al, 1999). For example, there were significant increases in the expression of NLRP3 and caspase-1 in blood cells from MDD patients (Alcocer-Gomez et al, 2014).…”
Section: The Inflammation Hypothesis Of Mood Disordersmentioning
confidence: 99%
“…In addition, treatment with trishomocubanyl and nido-1,2-carboranyl Cs significantly reduced depressivelike behaviours in mice in the FST, suggesting that these compounds are able to penetrate BBB and elicit antidepressant activity (Wilkinson et al, 2014). The same group has recently characterized a series of bioisosteres of adamantane benzamide and shown that several compounds with a BBB penetrability after administration via intravenous injection, including trifluorinated benzamide (compound 34) (Wilkinson et al, 2017). This compound blocks the human and mouse P2X7 receptors with IC50 values of 28 nM and 158 nM, respectively, in a Ca 2+ influx assay, or the human P2X7 receptor with IC50 value of 34 nM in a dye uptake assay.…”
Section: Other Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…To a lesser extent, expression of P2X 7 receptor has also been found in grey matter on astrocytes, oligodendrocytes, and neurons [11]. Moreover, it was shown that the radioligand [ 11 C]SMW139 selectively binds to the P2X 7 receptor with high affinity in preclinical in vivo studies and in post-mortem human tissues [8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell lysates were immunoblotted with anti-EE antibody. Proteins were detected at ~68, 31 and 58 kDa that corresponds to the expected molecular weights (MW) of P2X7A (solid arrow), P2X7E (chevron arrow), and P2X7L (thin arrow), respectively. Panels are from the same image with irrelevant lanes cropped out.…”
Section: Heteromeric P2x7l and P2x7a Complexes Are Expressed In Thementioning
confidence: 99%